EFL College Students' Skill in Using Collocations in Writing Essays - dewi nopita (Juliet, 2021)
Collocation is a natural order of words in which one word should be attached to another in a particular context. For students who learn English as a foreign language (EFL students), using collocations has been recognized to become a problem. This article is going to describe EFL college students’ skill in using collocations in writing essays. 42 students from the same class were selected. They were the 4th semester students of English Education Study Program at Teacher Training and Education Faculty of UMRAH who took Essay Writing course in the academic year 2019/ 2020. The students were given a take-home assignment to write essays. Then, the essays were analyzed to find out the students’ skill in using collocations. It was found that in using collocation in writing essays, 5 students had excellent skill, 14 students had good skill, and 23 students had low skill. The incorrect use of collocations consisted of lexical and grammatical collocations. Finally, it is hoped that these findings could be a useful input for future Essay Writing course.